Relative activity of hip and knee extensors in sprinting - implications for training - Wiemann, K.; Tidow, G. (New Studies in Athletics, 1995)
When looking for those muscles of the knees and hips which are responsible for the acceleration and horizontal velocity of the body during full-speed sprinting, the gluteus maximus, the adductor magnus, the hamstrings and the knee extensors have been identified as the most important ones. Electromyographic results concerning the degree of muscle activity (ROA) in 12 elite sprinters show that the hamstrings are active during the whole phase of hip extension (back-swing and support phase) while the gluteus maximus, like the knee extensors, "fire" only during the back-swing phase and the first half of the support phase. However, the adductor magnus has already ceased to be active at the beginning of the support phase. The peak ROA of the muscles examined are clearly above 100% of MVC activity. The adductor magnus shows a conspicuously high peak ROA of 200%. These findings, together with biomechanical considerations, lead to the suggestion that the hamstrings in particular, together with a muscle rein consisting of gluteus maximus and adductor magnus, supply the energy needed for forward propulsion, by providing a high back-swing velocity of the support leg. In this context the adductor magnus seems to be loaded to an especially high degree, The m. vastus medialis in general and the gluteus maximus, to some extent during the support phase, fulfil only anti-gravitation functions. This leads to corresponding implications for sprint training.